Examining the Causal Mediating Role of Brain Pathology on the Relationship Between Diabetes and Cognitive Impairment: The Cardiovascular Health Study. (8th May 2020) - Andrews, Ryan M.; Shpitser, Ilya; Lopez, Oscar; Longstreth, William T.; Chaves, Paulo H. M.; Kuller, Lewis; Carlson, Michelle C.
Summary: The paper examines whether diabetes mellitus leads to incident mild cognitive impairment and dementia through brain hypoperfusion and white matter disease. We performed inverse odds ratio weighted causal mediation analyses to decompose the effect of diabetes on cognitive impairment into direct and indirect effects, and we found that approximately a third of the total effect of diabetes is mediated through vascular-related brain pathology. Our findings lend support for a common aetiological hypothesis regarding incident cognitive impairment, which is that diabetes increases the risk of clinical cognitive impairment in part by impacting the vasculature of the brain.